Expectation and Reality: International Students' Motivations and Motivational Adjustments to Sustain Academic Journey in Chinese Universities - Mao, Yuezu; Ji, Hao; Wang, Rujia (Frontiers in Psychology, 2022)
Considering the increasing influx of international students to Chinese universities in recent decades, it is surprising to find that few empirical research, especially longitudinal ones, have been conducted in exploring the motivation of international students in China. To fill up the existing gap, this study explored and tracked international students’ motivations dynamically. Mixed research design, such as surveys, reflective journals, and interviews, was employed in this study. Data were collected from 671 international students and three teachers in three Chinese universities in Zhejiang province, mainland China on a longitudinal basis. The present study found that international students’ motivation could be discussed with considerations to the following two different phases: preliminary phase before they come to China and follow-up phase when they are in China. This study found that the integrative understanding of the external pulling force and the self-motivated pushing force plays a vital role in answering international students’ motivations to China. International students were driven more by the self-motivated pushing force than the external pulling force in selecting China as their study destinations. Moreover, international students experienced motivational changes when their expectations conflict with reality and their positive motivational adjustments and social interaction were important to the sustainability of their academic journey. Moreover, this study provides implications for the government, universities and international students in the aspects of policymaking, education and application.